Evolutionary Dynamics and Dissemination Pattern of the SARS-CoV-2 Lineage B.1.1.33 During the Early Pandemic Phase in Brazil - Resende, Paola Cristina; Delatorre, Edson; Gräf, Tiago; Mir, Daiana; Motta, Fernando Couto; Appolinario, Luciana Reis; Paixão, Anna Carolina Dias da; Mendonça, Ana Carolina da Fonseca; Ogrzewalska, Maria; Caetano, Braulia; Wallau, Gabriel Luz; Docena, Cássia; et al. (Frontiers in Microbiology, 2021)
A previous study demonstrates that most of SARS-CoV-2 Brazilian strains fell in three local clades that were introduced from Europe around the late February 2020. Here we investigated in more detail the origin of the major and most widely disseminated SARS-CoV-2 Brazilian lineage B.1.1.33. We recovered 190 whole viral genomes collected from 13 Brazilian states from 29th February to 31st April 2020 and combined them with other B.1.1 genomes globally sampled. Our genomic survey confirms that lineage B.1.1.33 is responsible for a variable fraction of the community viral transmissions in Brazilian states; ranging from 2% of all SARS-CoV-2 genomes from Pernambuco to 80% of those from Rio de Janeiro. We detected a moderate prevalence (5-18%) of lineage B.1.1.33 in some South American countries and a very low prevalence (<1%) in North America, Europe and Oceania. Our study reveals that lineage B.1.1.33 evolved from an ancestral clade, here designated B.1.1.33-like, that carries one of the two B.1.1.33 synapomorphic mutations. The B.1.1.33-like lineage may have been introduced from Europe or arose in Brazil in early February 2020 and few weeks later gave origin to the lineage B.1.1.33. These SARS-CoV-2 lineages probably circulated cryptically during February 2020 and reached all Brazilian regions and multiple countries around the world by mid-March, before the implementation of air travel restrictions in Brazil. Our phylodynamic analysis also indicates that public health interventions were partially effective to control the expansion of lineage B.1.1.33 in Rio de Janeiro because it median effective reproductive number (Re) was drastically reduced by about 66% during March 2020, but failed to bring it to below one. Continuous genomic surveillance of lineage B.1.1.33 might provide valuable information about epidemic dynamics and the effectiveness of public health interventions in some Brazilian states.